Developing augmented reality-based flashcards for early readers of elementary school - Adityas , M.Tolkhah; Aldina , Aldina; Ulfah, Amaliyah; Budairi , Ahmad (Universitas Ahmad Dahlan, 2024)
Reading is a foundational skill that students must master from the early stages of primary education. However, observations at SDN (Public Primary School) 22 Sulur Medan revealed that many first-grade students struggle with reading fluency and often confuse alphabet letters. To address this issue, this study aimed to develop Augmented Reality (AR)-based flashcards as an innovative learning tool to support beginner reading instruction. The research objectives include assessing the reading abilities of first-grade students at SDN 22 Sulur Medan, designing the AR-based flashcard media, and evaluating its feasibility. This study employed the ADDIE development model within the framework of research and development methodology. Data collection techniques included observations, expert validations (content, pedagogy, and media), as well as feedback from student and teacher questionnaires. The findings demonstrated high feasibility ratings for the AR-based flashcards: 88% for content validation, 83% for pedagogical validation, 91% for media validation, 95% for student responses, and 95% for teacher responses, resulting in an overall score of 90% in the